Comparing hybrid constructive heuristics for university course timetabling - Landa-Silva, Dario; Obit, Joe Henry (2011)
This extended abstract outlines four hybrid heuristics to generate initial solutions to the University course timetabling problem. These hybrid approaches combine graph colouring heuristics and local search in different ways. Results of experiments using two benchmark datasets from the literature are presented. All the four hybrid initialisation heuristics described here are capable of generating feasible initial timetables for all the test problems considered in these experiments.